2021
DOI: 10.1177/10556656211017795
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media and Hearing Loss in Patients With Nonsyndromic Craniosynostosis: A Multicenter Study

Abstract: Objectives: The objectives of this study were to: (1) determine the prevalence of otitis media with effusion in patients with nonsyndromic craniosynostosis; (2) determine the prevalence of hearing loss in patients with nonsyndromic craniosynostosis; and (3) identify potential patterns and outcomes in patients with nonsyndromic craniosynostosis. Methods: A retrospective chart review was conducted at 2 academic institutions, St Christopher’s Hospital for Children and SUNY Upstate Medical University, from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Though these outcomes are more commonly associated with syndromic cases [17, 19, 42, 43], some studies have explored the presence of chronic otitis media and hearing loss in the NSC population. Grewal et al [18] reported that 36% of their 113-patient NSC cohort had experienced at least one episode of otitis media, falling within the upper limit of normal when compared to historical rates among normocephalic children, and only 9% of NSC patients were found to have hearing loss; however, this study did not report a breakdown of prevalence rates by sex. Similarly, Prager et al [20] found 26% of 57 NSC patients presented with hearing loss, a frequency that was not significantly higher than the normal population of a similar age, and only a quarter of NSC patients with hearing loss were female.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Though these outcomes are more commonly associated with syndromic cases [17, 19, 42, 43], some studies have explored the presence of chronic otitis media and hearing loss in the NSC population. Grewal et al [18] reported that 36% of their 113-patient NSC cohort had experienced at least one episode of otitis media, falling within the upper limit of normal when compared to historical rates among normocephalic children, and only 9% of NSC patients were found to have hearing loss; however, this study did not report a breakdown of prevalence rates by sex. Similarly, Prager et al [20] found 26% of 57 NSC patients presented with hearing loss, a frequency that was not significantly higher than the normal population of a similar age, and only a quarter of NSC patients with hearing loss were female.…”
Section: Discussionmentioning
confidence: 69%
“…With these structural impacts on nearby anatomical features and the subsequent risk of increased ICP, craniosynostosis patients may present with consequent ophthalmological diagnoses, such as strabismus, papilledema, or exophthalmos [6][7][8][9][10]. Associations have also been reported with developmental delays, obstructive sleep apnea, chronic otitis media, hearing loss, chronic headaches, and seizure disorders [11][12][13][14][15][16][17][18][19][20][21]. Despite these correlations, substantial evolution in NSC management has led to improved outcomes in these patients, and the genetic pathophysiology of NSC craniosynostosis is becoming increasingly better understood with the development of next-generation sequencing technologies [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Between the ages of 3 and 5, the rapid growth of the nasopharynx's soft tissue can constrict the nasopharyngeal airway. However, as the nasopharynx opens, the soft tissues are largely spared (3). Factors like allergies and environmental toxins can induce adenoid hypertrophy, causing the adenoid tissue to enlarge when exposed to allergens and irritants.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study examined the impact of probiotics on the incidence of otitis media in children with cleft lip and/or palate (CL/P), a birth defect with highest susceptibility to recurrent otitis media [23,24]. Probiotics have been thoroughly examined for the prevention of childhood otitis media [16,17]; however, the potential bene ts in children with CL/P remain unclear.…”
Section: Introductionmentioning
confidence: 99%